INFLUENCE OF IMPERFECT CONTACT CONDITIONS ON THE TORSIONAL WAVE DISPERSION IN PRE-STRAINED MANY LAYERED HOLLOW CYLINDER MADE OF HIGHLY ELASTIC MATERIALS - Karafaki, Eyyup; Kepceler, Tamer (YILDIZ TECHNICAL UNIV, 2020)
In this paper, influence of the bonded imperfectness on torsional wave dispersion in the finitely pre-strained hollow compound circular cylinder made of highly-elastic material were investigated. The investigations are carried out within the scope of the piecewise homogeneous body model with the use of the Three-dimensional Linearized Theory of Elastic Waves in Initially Stresses Bodies (TLTEWISB). The mechanical relations of the materials of the cylinders are described through the harmonic potential. Numerical results on the effects of the imperfectness of the boundary condition on the influence of the initial stresses on the wave propagation velocity are presented and discussed.
Keywords: Torsional wave dispersion; imperfect contact condition; initial stress; compounded cylinder; PROPAGATION; INTERFACE; Engineering